Clinical characteristics of Plasmodium vivax malaria infection in children and adolescents in the Republic of Korea during the period 2000 to 2016: a retrospective study - Jung Ah Lee; Je Eun Song; Seong Yeon Park; Yoon Soo Park; Yoonseon Park; Yee Gyung Kwak; Sang-Eun Lee; Hyun-Il Shin; Joon-Sup Yeom (BMC Infectious Diseases)
Abstract Background Although Plasmodium vivax (P. vivax) malaria is in the pre-elimination phase in the Republic of Korea (ROK), it continues to affect children and adolescents, who account for approximately 4–6% of the 300 to 500 annual cases. Despite this, research focusing on P. vivax malaria in this particular population remains limited. This study investigates the clinical characteristics of pediatric P. vivax malaria in the ROK from 2000 to 2016. Methods We retrospectively analyzed pediatric patients aged 0–18 years, diagnosed with P. vivax malaria in five hospitals in Goyang City and Seoul. Data on demographics, clinical presentations, treatment regimens, and outcomes were collected. Statistical analyses were performed for comparisons between severe and non-severe cases, across age groups, and assessing trends over time. Results A total of 156 pediatric cases of indigenous P. vivax malaria were diagnosed. The median patient age was 13 years (men: 64.7%). Severe malaria occurred in 13.5% patients, predominantly in adolescents aged 15–18 years. The most common severe manifestations were jaundice (57.1%) and anemia (33.3%). In the ROK, the treatment regimen for pediatric P. vivax malaria involves oral administration of chloroquine at a dose of 25 mg base/kg divided over 3 days, followed by primaquine at a dose of 0.3 mg/kg for 14 days. Although all patients received chloroquine, a higher proportion of younger patients received a dose less than 25 mg/kg (87.5%, 85.5%, and 58.6% of those aged 0–4, 5–14, and 15–18 years, respectively; p < 0.001). Parasite clearance time (PCT) increased over the years, suggesting a potential decline in the chloroquine sensitivity of P. vivax. No deaths or significant long-term complications were reported. Conclusions Pediatric P. vivax malaria showed a low incidence of severe cases and no mortality in the ROK. Underdosing of antimalarial drugs was observed, underscoring the need for educating healthcare providers to ensure appropriate dosing. Increasing PCT highlights the need for ongoing surveillance of drug efficacy in this population. Further research on the evolving sensitivity of P. vivax and improved treatment protocols is thus essential.